Meningkatkan Kemandirian Anak Melalui Model Pembelajaran Project Based Learning Kelompok A Di Raudhatul Athfal Harapan Ibu Desa Labat Muara - Normila Normila; Muhammad Yusuf; Noor Baiti (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to improve children's independence through the implementation of the Project Based Learning (PjBL) model in Group A at Raudhatul Athfal Harapan Ibu, located in Labat Muara Village. Independence is a crucial aspect of early childhood development, reflecting a child’s ability to carry out activities without relying on others. The Project Based Learning model was chosen because it provides active, meaningful, and contextual learning experiences through project activities that directly involve children. This research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The subjects of the study were 15 children from Group A. Data collection instruments included observation, documentation, and field notes. In the first cycle, the children created pencil holders from cardboard and used straws, while in the second cycle, they decorated the pencil holders with flannel fabric. The results showed a significant improvement in the children’s independence after implementing the Project Based Learning model. Therefore, it can be concluded that Project Based Learning is effective in enhancing the independence of early childhood learners at Raudhatul Athfal Harapan Ibu